Long-term follow-up of acute lymphoblastic leukemia in young children treated by the SCMC-ALL-2009 protocol. Issue 12 (14th October 2020) - Liu, Kangkang; Chu, Jinhua; Dai, Yu; Jiang, Aoshuang; Yang, Linhai; Xie, Zhiwei; Zhang, Kunlong; Tu, Songji; Cai, Huaju; Wu, Zhengyu; Wang, Ningling
Abstract: This study evaluated the long-term therapeutic effect and prognostic factors of acute lymphoblastic leukemia (ALL) in 100 young Chinese children (<2 years old) who were enrolled in the Shanghai Children's Medical Center (SCMC)-ALL-2009 study in five pediatric hematological disease centers based on collaboration. The 5-year and 10-year event-free survivals (EFS) were 74.7 ± 3.2% and 73.3 ± 3.4%. The 10-year EFS rates for low risk, intermediate-risk, and high-risk patients were 81.9 ± 5.0%, 71.3 ± 4.3%, and 22.2 ± 13.9%, respectively. Relapse occurred in 19 patients. MRD results on day 55, good or poor response to prednisolone, and age at diagnosis were shown to have important prognostic and therapeutic implications. Compared with the SCMC-ALL-2005 protocol, showed that the 10-year-EFS and 10-year-overall survival of the SCMC-ALL-2009 protocol were better than that of the −2005 protocol. Notably, the intermediate-risk group was improved after the chemotherapy intensity was strengthened.